Bercak Merah di Kepala di Diagnosis Banding sebagai Tinea Kapitis pada Bayi Usia 2 Bulan di Pedalaman - M. Gazali Hafid (Pusat Riset dan Inovasi Nasional, 2024)
Tinea capitis is the most common dermatophytosis in children. Culture examination is still the gold standard for confirming the diagnosis of tinea capitis, but this examination couldn’t be always done, especially in areas that did not have mycological examination. There is very little data and literature on infants.a male infant, 2 months old, with complaints of red patches on the scalp, skin around the red area, peeling, hair not growing since 1 month ago. Dermatological examination of the vertex region revealed a solitary erythema macular efflorescence, well-defined, round in shape, 2- 6 cm in diameter, with dull grayish hair, 0.5-1 cm above the scalp surface, covered with thin scales, and yellowish crusts. Wood's lamp examination showed greenish fluorescence. 10% KOH examination of hair taken at the lesion site revealed no hyphae or spores. The patient was differential diagnosed as gray patch tinea capitis and treated with 2% ketoconazole ointment. The patient controlled 2 weeks later and the complaint improved, the crusts disappeared and the red patches shrunk. Therefore, therapy was continued. Diagnosis of tinea capitis in infant requires culture examination with complete materials at the first level of health care facilities, in order to managed it properly.